Aromatic hydroxylations over titanium-substituted crystalline silicates - Wilkenhöner, Uwe (Department of Chemical Engineering, 2023)
This work focuses on aromatic hydroxylations over titanium-substituted zeolites of different pore sizes (TS-1, Al-free Ti-beta and Ti-HMS) using aqueous H2O2 as the oxidant. The aim was to gain a deeper understanding of the key factors controlling activity and selectivity, which implied an investigation of the reaction kinetics and the adsorption and diffusion properties of reactants and products in the various catalysts using different solvents. The role of shape selectivity inside the micropores of the solids and the reaction at their external surface was also examined.